2011
DOI: 10.1007/dcr.0b013e3181f46810
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience and Satisfaction With Sacral Neuromodulation: Results of a Single-Center Sample Survey

Abstract: This study shows that patients treated with sacral neuromodulation, in general, are very satisfied. The main problems mentioned by patients are pain, loss of efficacy, and general concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
2
11
0
1
Order By: Relevance
“…From these, only seven articles published between 2001 and 2015 contributed to the systematic review, providing data on outcomes in a total of 375 patients (range 21–117 patients per study) (Table . Specific exclusions after full‐text review (and after exclusion of non‐English language publications: n = 1) included nine studies where the population sample was confirmed to be less than 20 patients , one study which was a dual publication reporting a patient cohort that overlapped with another study and one study where results were combined for mixed indication s . Study follow up ranged from 20 to 51 months.…”
Section: Introductionmentioning
confidence: 99%
“…From these, only seven articles published between 2001 and 2015 contributed to the systematic review, providing data on outcomes in a total of 375 patients (range 21–117 patients per study) (Table . Specific exclusions after full‐text review (and after exclusion of non‐English language publications: n = 1) included nine studies where the population sample was confirmed to be less than 20 patients , one study which was a dual publication reporting a patient cohort that overlapped with another study and one study where results were combined for mixed indication s . Study follow up ranged from 20 to 51 months.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated short-and medium-term success [4][5][6][7][8][9][10][11][12][13][14][15] and a double-blind crossover study has shown that this is not due to a placebo effect [16]. SNS improves quality of life [17][18][19][20][21][22], with high levels of satisfaction [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…We have documented a clear relationship between patient satisfaction and clinical outcome assessed by the widely used symptom scores, bowel‐habit diaries and patient self‐reported overall bowel function, social function and quality of life. In a recent exploratory study, it has been shown that patient satisfaction with SNS therapy was explained both by patient perception of present bowel function and quality of life [23]. An unexpected finding in this study was that 46% of the patients with more incontinence episodes at follow‐up than at baseline were satisfied with the treatment result.…”
Section: Discussionmentioning
confidence: 57%